Polymer adsorption in laminar tube flow of drag reducing fluids. - Son, Jae Ek. (University of Ottawa (Canada), 1978)
The results of an experimental investigation concerned with the characterization of polymer adsorption and flow behaviour in the vicinity of the tube wall during steady uniform laminar flow are reported. Two Polyox homologues (Coagulant and WSR 301) have been tested at various concentrations (10 to 100 ppm) and flow rates. Measurements were conducted using five different tube diameters to study the effect of the tube size on the polymer adsorption onto the wall. 0.3M K2SO4 aqueous solution was employed as a poor solvent to investigate the effect of polymer coiling (in solution) on the polymer adsorption. The degree of coiling was inferred by the measurement of intrinsic viscosity. Polymer degradation was also measured with duration of time. A considerable decrease in viscosity and in polymer adsorption (anomalous zone thickness) in tube was observed with an increase in the duration of a dilute polymer solution. The thickness of the anomalous zone associated with polymer adsorption in laminar flow of a dilute polymer solution in a tube was correlated with the drag reduction manifested in turbulent flow by a mathematical equation with macromolecular size and tube diameter as parameters. The data suggested that the polymer adsorption could be a fundamental basis for the turbulent drag reduction phenomenon.
Keywords: Engineering, Chemical.